2020
DOI: 10.1002/cpt.1953
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Exposure–Response Relationship for Therapeutic Monoclonal Antibodies in Immuno‐Oncology and Beyond: Challenges, Perspectives, and Prospects

Abstract: Recent data from immuno-oncology clinical studies have shown the exposure-response (E-R) relationship for therapeutic monoclonal antibodies (mAbs) was often confounded by various factors due to the complex interplay of patient characteristics, disease, drug exposure, clearance, and treatment response and presented challenges in characterization and interpretation of E-R analysis. To tackle the challenges, exposure relationships for therapeutic mAbs in immuno-oncology and oncology are reviewed, and a general fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(120 citation statements)
references
References 65 publications
5
111
0
Order By: Relevance
“…Recognizing and accounting for the impact of time-varying clinical response and prognostic factors on exposure are critical for accurate E-R interpretations. 49 This relationship is illustrated by the findings for nivolumab, avelumab, durvalumab, and pembrolizumab where patients with improved post-treatment disease status showed greater time-dependent decreases in drug CL. [7][8][9][10] The mechanism is not fully understood, but there is an interaction between clinical response, prognostic factors, and exposure.…”
Section: Discussionmentioning
confidence: 96%
“…Recognizing and accounting for the impact of time-varying clinical response and prognostic factors on exposure are critical for accurate E-R interpretations. 49 This relationship is illustrated by the findings for nivolumab, avelumab, durvalumab, and pembrolizumab where patients with improved post-treatment disease status showed greater time-dependent decreases in drug CL. [7][8][9][10] The mechanism is not fully understood, but there is an interaction between clinical response, prognostic factors, and exposure.…”
Section: Discussionmentioning
confidence: 96%
“…OS is often the primary response endpoint for oncology trials, and its relationship with exposure is confounded by prognostic factors. Recognizing and accounting for the impact of time‐varying clinical response and prognostic factors on exposure are critical for accurate E‐R interpretations 55 . This relationship is illustrated by the findings for nivolumab, avelumab, durvalumab, pembrolizumab and ipilimumab, where patients with improved post‐treatment disease status showed greater time‐dependent decreases in drug CL 7–11 .…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that the exposure-efficacy relationship for antibody-drug conjugates might be confounded (especially conducted at a single dose level) by prognostic factors similar to other mAbs, for which the conjugate exposure tends to be lower in patients with poor prognostic factors who generally also have poor efficacy because of their sicker disease status. 38 Although it is not considered a key analysis to support T-DM1 dose, exposure-response analysis with the unconjugated payload (DM1) exposures showed that no significant relationship was observed between these observed exposure metrics and efficacy or safety end points at the 3.6 mg/kg T-DM1 dose. 32 Semimechanistic longitudinal PK/PD analysis of linking the conjugated antibody PK profile with the time course of PD end points (eg, platelet count decrease 35 or ALT/AST elevation 36,37 ) provided additional insight to support 3.6 mg/kg every 3 weeks as a well-tolerated dose with minimal dose delays or reductions for thrombocytopenia, AST, and ALT, based on the rigorous simulations with the dose modification rules incorporated for T-DM1.…”
Section: Impact On Decision-making In Drug Developmentmentioning
confidence: 99%
“…The analysis supported the approved T‐DM1 dose (3.6 mg/kg once every 3 weeks), which demonstrated a positive benefit/risk ratio versus control, even for the patients in the lowest exposure quartile. It is worth noting that the exposure‐efficacy relationship for antibody‐drug conjugates might be confounded (especially conducted at a single dose level) by prognostic factors similar to other mAbs, for which the conjugate exposure tends to be lower in patients with poor prognostic factors who generally also have poor efficacy because of their sicker disease status 38 . Although it is not considered a key analysis to support T‐DM1 dose, exposure‐response analysis with the unconjugated payload (DM1) exposures showed that no significant relationship was observed between these observed exposure metrics and efficacy or safety end points at the 3.6 mg/kg T‐DM1 dose 32 .…”
Section: Population Pk/pd and Exposure‐response Modeling For Antibodymentioning
confidence: 99%